Blown-extrusion of biodegradable active packaging with food preservatives: Packaging properties, food quality and safety - Wongphan, Phanwipa; Harnkarnsujarit, Nathdanai; Vera Estacho, Paula; Canellas Aguareles, Elena; Nerín de la Puerta, Cristina (Jornada de Jóvenes Investigadores del I3A, 2023)
This research aimed to develop biodegradable films from polymer blended film containg food preservatives. 1H-NMR and FTIR showed that the added preservativesmodified the chemical structure, leading to modified film properties. Accordingly, these food preservatives effectively enhanced functionality of films and maintained quality and safety, thus improving food quality and safety.